TREATMENT OUTCOMES OF MULTIDRUG RESISTANT TUBERCULOSIS PATIENTS IN EAST JAVA FROM 2014 TO 2017 - Lailatul Fitriya; Kurnia Dwi Artanti (Universitas Airlangga, 2020)
Background: Multidrug resistant tuberculosis (MDR TB) is a major public health problem marked by the Mycobacterium tuberculosis strain that is resistant to first line anti TB drugs, including rifampicin and isoniazid simultaneously. A patient confirmed as having MDR TB can transmit this form of TB to other individuals. Therefore, treatment success is the main target when addressing MDR TB. Purpose: This study aimed to assess the treatment outcomes of MDR TB patients in East Java Province from 2014 to 2017. Method: This is a quantitative-descriptive study using the secondary data of drug resistant TB patients sourced from the e-TB Manager website in the East Java Province Health Office. Results: The results show that the average MDR TB patients was 47 years old, 57.44% were male, 37.52% had a negative HIV status, 44.87% were relapse patients, 71.95% had undergone two or less previous treatments, and 69.24% had sputum culture conversion. The treatment outcomes included 161 patients (31.14%) confirmed as cured, 27 patients (5.22%) completing treatment, 174 patients (33.65%) defaulting, two patients (0.38%) confirmed as having failed treatment, and 59 patients (11.41%) dying during the treatment period. Conclusion: The treatment success rate was low and the number of defaults was high. Therefore, it is hoped that there will be support from those closest to the patient and health workers who will maintain and increase the patient's motivation to complete the treatment.